Exploring genetic diversity for heat tolerance among lentil (Lens culinaris Medik.) genotypes of variant habitats by simple sequence repeat markers. Issue 2 (1st February 2016) - Singh, Dharmendra; Singh, Chandan K.; Tomar, Ram Sevak S.; Chaturvedi, Ashish K.; Shah, Divya; Kumar, Arun; Pal, Madan
Abstract: The study was carried out to assess genetic diversity among 119 lentil genotypes grown in different habitats for heat tolerance using morpho‐physiological and reproductive traits and SSR markers. High‐temperature stress was applied at seedling (35/33°C) and anthesis stages (35/20°C) to study the effects on morpho‐physiological and reproductive traits under hydroponic condition, which was compared with non‐stressed and stressed field conditions. A set of 209 alleles were identified by 35 SSR markers among the genotypes. Genetic diversity and polymorphism information content values varied between 0.0494–0.859 and 0.0488–0.844, with mean values of 0.606 and 0.563, respectively. Genotypes were clustered into nine groups based on SSR markers. Morpho‐physiological and reproductive traits under heat stress were found to be significantly different among SSR clusters. These findings suggest that heat adaptation is variable among the genotypes and the tolerant materials can be evolved through hybridization using parents from different clusters with diverse mechanisms of heat tolerance.